Current clinical trials testing the combination of immunotherapy with radiotherapy. Issue 1 (December 2016) - Kang, Josephine; Demaria, Sandra; Formenti, Silvia
Abstract Increasing evidence demonstrates that radiation acts as an immune stimulus, recruiting immune mediators that enable anti-tumor responses within and outside the radiation field. There has been a rapid expansion in the number of clinical trials harnessing radiation to enhance antitumor immunity. If positive, results of these trials will lead to a paradigm shift in the use of radiotherapy. In this review, we discuss the rationale for trials combining radiation with various immunotherapies, provide an update of recent clinical trial results and highlight trials currently in progress. We also address issues pertaining to the optimal incorporation of immunotherapy with radiation, including sequencing of treatment, radiation dosing and evaluation of clinical trial endpoints.